Effect of Nitrogen Fertilizer on Soil Nutrient Concentration, Plant Nutrient Concentration and Fruit Setting in Pummelo (Citrus grandis (L.) Osbeck) cv. Thong Dee อิทธิพลของปุ๋ยไนโตรเจนต่อปริมาณธาตุอาหารในดิน ปริมาณธาตุอาหารในใบ และการติดผลของส้มโอพันธุ์ทองดี - Nartvaranant, Pongnart (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2020)
The research objective was to study the effect of different proportions of nitrogen fertilizer application on soil nutrient concentration, plant nutrient concentration and fruit set in pummelo (Citrus grandis (L.) Osbeck) cv.Thong Dee. The experiment was laid out in a Completely Randomized Design (CRD) with 4 treatments and 5 replications. Treatments consisted of N applied at 100, 75, 50, 125 %N. Basal dose of phosphorus (P2O5) as single super phosphate and potassium (K2O) as potassium chloride (KCl) were given to all plants. The N fertilizer treatments were applied in three equal doses to the pummelo trees by soil application. The experiment was conducted at pummelo orchards in Nakhon Prathom province. The results showed that nitrogen fertilizer with different percentage of nitrogen had no effect on soil nitrogen, phosphorus and potassium concentrations (p > 0.05) but there were significant difference in leaf nutrient concentration. 75 and 50 %N gave the highest leaf N concentration during 1 month before harvest (p < 0.05) but it had no effect on leaf phosphorus and potassium concentration. For fruit quality and fruit setting, 50 %N gave the highest TSS:TA ratio (27.81) following by 75 %N (23.96), 100 %N (19.14) and 125 %N (15.22) respectively. While, there were no effect on fruit sizes, fruit weights, TSS and TA. Moreover, for percentage of fruit setting, 50 %N and 75 %N gave the highest percentage of fruit setting at 55 and 51%, followed by 100 %N (25%) and 125 %N (19%) respectively. Therefore, it was concluded that nitrogen fertilizer contained 50% N, which used by the farmer, was suitable for plant growth and fruit setting in pummelo cv. Thong Dee.